Gaps in Mental Health Care for Youth With Rheumatologic Conditions: A Mixed Methods Study of Perspectives From Behavioral Health Providers. Issue 5 (8th April 2019) - Knight, Andrea; Vickery, Michelle; Faust, Lauren; Muscal, Eyal; Davis, Alaina; Harris, Julia; Hersh, Aimee O.; Rodriguez, Martha; Onel, Karen; Rubinstein, Tamar; Washington, Nina; Weitzman, Elissa R.; et al.
Abstract : Objective: To identify behavioral health provider perspectives on gaps in mental health care for youth with rheumatologic conditions. Methods: Social workers (n = 34) and psychologists (n = 8) at pediatric rheumatology centers in the Childhood Arthritis and Rheumatology Research Alliance (CARRA) completed an online survey assessing current practices and mental health care needs of youth with rheumatologic conditions. Responses were compared to a published survey of CARRA rheumatologists (n = 119). Thematic analysis of 20 semi‐structured interviews with behavioral health providers was performed. Results: One‐third of CARRA centers (n = 100) had no affiliated social worker or psychologist. Only 1 behavioral health provider reported current universal mental health screening at their rheumatology clinic, yet routine depression screening was supported by >85% of behavioral health providers and rheumatologists. Support for anxiety screening was higher among behavioral health providers (90% versus 65%; P < 0.01). Interviews illustrated a need for interventions addressing illness‐related anxiety, adjustment/coping/distress, transition, parent/caregiver mental health, and peer support. Limited resources, lack of protocols, and patient cost/time burden were the most frequent barriers to intervention. Inadequate follow‐up of mental health referrals was indicated by 52% of providers. More behavioral health providers than rheumatologists favored mental health services in rheumatology settings (55% versus 19%; P < 0.01). Only 7 social workers (21%) provided counseling/therapy, and interviews indicated their perceived underutilization of these services. Conclusion: Behavioral health providers indicated an unmet need for mental health interventions that address illness‐related issues affecting youth with rheumatologic conditions. Implementation of mental health protocols and optimizing utilization of social workers may improve mental health care for these youth.